Advances towards Decolonizing Global Health - Matagi, Salim Omambia (New Advances in Medicine and Medical Science Vol. 6, 2023)
The objective of this research is to sensitize Global health equity, accessibility, and affordability. The truth is always one: no matter the interpretations, versions, perceptions or perspectives. The science of medicine existed eons ago and was trusted to heal and reverse ailments as well as save lives, according to the bulk of scientific or historical data. Aside from the financial costs of the business, a great deal of time has been and continues to be committed in developing better diagnostic and treatment improvements around the world. Surprisingly, the rich as well do not have much faith in conventional medicine; the bourgeois have the majority of their population believing in the notion, which was attributed to the fact that the majority of the bourgeois work so hard and some even impersonate the rich. LMICs must embrace and implement data-driven decisions, as well as be efficient leaders and managers in their own countries, because they know and understand their countries best. External expertise can help with evaluations, audits, and case studies to aid with the strategies for reaching the goal.